Augmenting Function for Infarction from Infection: Impella 2.5 for Ischemic Cardiogenic Shock Complicating Sepsis. (5th February 2017) - George, Praveen; Srivastava, Mukta C.; Ludmir, Jonathan; Reed, Robert M.; Tewelde, Semhar Z.; Gupta, Anuj; McCurdy, Michael T.
Abstract : Cardiac dysfunction is a common complication of sepsis in individuals with preexisting coronary disease and portends a poor prognosis when progressing to ischemic cardiogenic shock. In this setting, maximal medical therapy in isolation is often inadequate to maintain cardiac output for patients who are poor candidates for immediate revascularization. Furthermore, the use of vasopressors and inotropes increases myocardial demand and may lead to further injury. Percutaneous ventricular assist devices provide a viable option for management of severe shock with multiorgan failure. The Impella is one of several novel mechanical support systems that can effectively augment cardiac output while reducing myocardial demand and serve as a bridge to recovery from severe hemodynamic compromise. This case report describes the successful utilization of the Impella 2.5 in a patient with baseline profound anemia and coronary artery disease (CAD) presenting in combined distributive and cardiogenic shock associated with a type 2 myocardial infarction complicating sepsis.